Kontribusi Mahasiswa dalam Pendampingan Bimbingan Belajar di Desa Kletekan - Pratiwi Novitasari; Amiratih Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2023)
Learning guidance assistance for students is one of the ways used to improve student learning outcomes. There are two factors that influence student learning outcomes, namely internal factors and external factors. Internal factors are factors from within the student such as the student's willingness to learn, while external factors are factors from outside the student's self such as the learning atmosphere. The purpose of carrying out tutoring assistance by STKIP Modern Ngawi students for students is that it is expected to be able to increase student motivation in learning so that student abilities increase with a maximum and enjoyable learning process. Learning guidance assistance is carried out in four stages, namely: (1) Providing practice questions to determine students' basic abilities, (2) Providing motivation to learn to students, (3) Providing material explanations to students, (4) Question and answer to find out students' abilities after the learning assistance activities have been completed. The results of the tutoring assistance had a positive impact which was marked by high student enthusiasm and increased learning outcomes.